Atypical Epithelial Changes in Seminal Vesicles - Arias Stella, Javier (1959)
The morphological characteristics of atypical epithelial disruption occurs in the seminal vesicle are described. The lesion is mainly characterized by focal areas in which there is marked nuclear hypertrophy and some degree of epithelial hyperplasia. The exioliadas hypertrophic cells can be confused with neoplastic cells. The alteration occurs mostly after the fourth decade. Inflammation and vascular sclerosis in the seminal vesicle, prostate gland hyperplasia, abnormality or atrophy of the testes, or pathological processes in each case apparently unrelated to the presence of the disturbance.